Students’ Perception on The Use of Instagram to Learn English Vocabulary - Sitti Fitriawati Mamudi; Thia Chania S Alamry (Sintuwu Maroso Journal of English Teaching, 2021)
This study aimed to determine students' perceptions on the using of Instagram to learn English vocabulary. This type of research used qualitative research. The subjects used in this research were 20 students of various ages and who have followed an English learning account on Instagram. Data collection techniques in this research used questionnaire, interview, and documentation as supporting data which is needed in triangulation. Based on the research results obtained from students' perceptions of using Instagram for learning English vocabulary, it really helped the participants in adding new vocabulary that they got by following the English vocabulary learning account on Instagram. It can be interpreted that learning English on Instagram got a postive response by the participants and it can be used as a good choice in English learning media